ANTIMICROBIAL ACTIVITY OF STILBENOIDS AND FLAVONOIDS FROM THREE SPECIES OF COMBRETACEAE - Katerere, D.; Gray, A.; Nash, R.; Waigh, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Four phenanthrenes, one of them new, were isolated from the fruit of Combretum hereroense and one from the leaves of C. collinum. Three of them were moderately active against Candida albicans, Mycobacterium fortuitum and Staphylococcus aureus in the microplate assay. Four bibenzyls, one of which is novel, two chalcones, three flavanones and a flavone, all previously unreported from Combretaceae, were isolated from the leaves of C. apiculatum Engl. & Diels and two were isolated from the leaves of C. collinum. Pinocembrin, one of the ten compounds from C. apiculatum, had good activity against S. aureus and excellent activity against C. albicans in agreement with literature reports.